Process Improvement in Newspaper Printing through Lean Six Sigma: Waste Analysis and Defect Reduction Strategies - Haiqal Alif; Aijaz Ahmad Bhat (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2024)
This study examines the implementation of Lean Six Sigma (LSS) in a newspaper production company in Malaysia to identify and analyze sources of waste and product defects. Using the DMAIC (Define–Measure–Analyze–Improve–Control) framework—applied up to the DMAI stages—the research integrates qualitative methods (interviews and observations) with quantitative tools (control charts, Value Stream Mapping, and sigma metrics). The results revealed two dominant waste categories: waiting time and defective products. Value Stream Mapping indicated that only 55.32% of the total lead time contributed to value-added activities, while 44.68% consisted of non-value-added or necessary non-value-added processes. Over one year, the company produced 840,000 copies with 12,000 defective products (1.43%), primarily scattered ink (55%), uneven margins (25%), and ink misregistration (20%). The overall process capability achieved an average DPMO of 4,833 and a sigma level of 4.09, indicating stable yet improvable performance. Root cause analysis highlighted human factors as the most influential source of defects, followed by machine, material, and method-related issues. Improvement strategies focusing on operator training, SOP compliance, preventive maintenance, and stricter supervisory controls. This study contributes theoretically by extending the application of LSS to the printing industry and practically by offering actionable recommendations to enhance production quality and efficiency. Future research should implement these strategies and validate their effectiveness through the Control stage of DMAIC.